An Investigation Into the Role of English as a Foreign Language Teachers’ Self-Efficacy in Their Organizational Commitment - Gao, Yuan (Frontiers in Psychology, 2022)
The way EFL students experience the process of learning has always been of utmost importance since it tremendously affects the amount of learning and received pleasure throughout this process for both teachers and students. From this aspect, both self-efficacious and committed teachers make a contribution to their organization’s success. Even though many studies have been conducted about teachers’ self-efficacy and their organizational commitment, a few of which concentrate their attention on the link between these two variables. To fill this gap, this review paper provides a glimpse at the underlying roles of teacher self-efficacy and their organizational commitment. Furthermore, it presents the definitions and applications of each construct. Finally, some implications and future recommendations are put forward to avid scholars.